Biometria de sementes, morfologia de plântulas e crescimento inicial de mudas de quimiotipos de Myracrodruon urundeuva Allemão - Girão, Karen Thomeny (2013)
The species Myracrodruon urundeuva Allemão has high economic value due to its wide use in industry and in folk medicine, in addition to presenting a great potential to be used in reforestation programs. This study aimed to generate information regarding morfobiometria seed, seedling morphology and seedling growth of four chemotypes M. urundeuva Allemão. The research was conducted at the Center for Teaching and Research in Urban Agriculture (NEPAU), Department of Plant Science in CCA/UFC, Fortaleza - CE. The biometric study of seeds aimed to study the external morphology and quantification of thousand seed weight of each chemotype. We used a sample of 100 seeds, where the following characteristics were observed: biometrics, color, shape, texture and thousand seed weight. About the morphology, it was not detected distinction between the chemotypes. The chemotypes called by CE3, RN3, RN2 and RN2’ showed an average diameter of, respectively, 3.80 mm, 3.35 mm, 3.79 mm and 3.15 mm. The morphological characterization of germination of seedlings aimed to study the morphology of germination of the four chemotypes. For this study, 100 seeds of each chemotype were seeded in 300 ml plastic cups filled by mixture of vermiculite and humus. All chemotypes showed membranous epicarp and epigeal phanerocotylar showing further development of roots in relation to shoot. The experimental testing of initial growth aimed to evaluate the effect of two environments in eight periods of the four mastic chemotypes. The experiment was conducted in completely randomized design (CRD) in sub-split plots with plots consisting of the environments (greenhouse and full sun), the split the chemotypes (CE3, RN3, RN2 and RN2’), and sub-subplots, the evaluation periods (0, 14, 28, 42, 56, 70, 80 and 98 days after transplanting). The variables evaluated were: shoot length, root length, leaf number, stem diameter, dry weight of shoot and root dry weight. The present study showed that the environment full sun is best suited to the cultivation of chemotypes analyzed.